Implementation of deep learning strategy in islamic religious education to internalize islamic values at smk hisba buana semarang - Slamet Panuntun; Belina Hendri Saputri; Moh. Fahsin; Inas Umniyah; Inayatul Farihah; Masykur (At Turots: Jurnal Pendidikan Islam, 2025)
Islamic Religious Education (PAI) in Vocational High Schools (SMK) faces challenges in shaping students' character to excel not only in vocational competencies but also in moral and spiritual integrity. The deep learning strategy is considered effective in addressing these challenges as it emphasizes deep conceptual understanding, emotional engagement, and reflective capacity toward Islamic values. This study aims to analyze the implementation of the deep learning strategy in PAI learning and its role in internalizing Islamic values in the daily lives of SMK students. The research adopts a descriptive qualitative approach, conducted at SMK Hisba Buana Semarang, focusing on 11th-grade PAI classes with the topic "Work Ethic in Islam." Data were collected through observation, interviews, and document analysis. The results indicate that this strategy is implemented through contextual approaches, in-depth discussions, habituation of Islamic values, and personal reflection. This strategy facilitates meaningful internalization of values, particularly related to work ethics, responsibility, and integrity. Its advantages include active student participation, reflective value awareness, and real-life relevance. The challenges encountered involve extended time requirements, high pedagogical demands, and varying levels of students’ reflective abilities. Proposed solutions include flexible planning, teacher training, and small group mentoring. Thus, this strategy holds great potential as an innovative approach to PAI learning in vocational schools